Republic of Mozambique : Fourth Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria: Staff Report; Debt Sustainability Analysis; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Mozambique. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The Mozambican economy recorded a strong performance in 2011, showing little sign of being affected by the global turmoil. Given the declining trend in foreign aid in the medium term, the government is tapping more into nonconcessional borrowing to close the infrastructure gap. To promote inclusive growth, the government has launched a series of initiatives to implement the Poverty Reduction Strategy including an overhaul of social protection programs. Reform momentum needs to be maintained, as implementation challenges are enormous and administrative capacity and coordination need to be upgraded.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet